Effectiveness of Worksheets of Biology Students of High School Based On Critical Thinking Skills in Virus Concept - Hidayati Hidayati; Muhammad Zaini; Kaspul Kaspul (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2020)
The 2013 curriculum learning process includes three domains, namely affective (attitude), cognitive (knowledge), and psychomotor (skills). This study aims to develop a valid, practical, and effective Student Worksheet. The research method used is the Tessmer design, which consists of (1) Expert review; (2) one-to-one; (3) small group. Validation subjects were three experts, individual subjects were three students in class X in high school and small group test subjects were six students in class X in high school. The results showed that: (1) the validity of LKPD based on expert testing had a valid category with an overall average of 3.59; (2) the practicality of the contents of LKPD has a good category with an overall average of 3.70 and the practicality of the LKPD's expectations based on the responses of students has a very good category with an overall average of 88.70%; and (3) the effectiveness of LKPD based on the assessment of students' critical thinking skills in working on LKPD has both categories (including interpretation) and very good categories (includes analysis, evaluation, inference, explanation, and self-regulation). Interpersonal skills (collaborating) of students have a very good category with a score of 86.33% and intrapersonal skills (conscientious) students have a very good category with a score of 88.33%.AbstrakProses pembelajaran kurikulum 2013 mencakup tiga ranah, yaitu afektif (sikap), kognitif (pengetahuan) dan psikomotor (keterampilan). Penelitian iniobertujuan untuk mengembangkan Lembar Kerja Peserta Didik yang valid, praktis dan efektif. Metode penelitian yang digunakan yaitu desain Tessmer, yang terdiri atas 1) Expert review; 2) one-to-one; 3) small group. Subjek validasi adalah 3 orang ahli, subjek perorangan adalah 3 orang peserta didik kelas X jenjang SMA dan subjek uji kelompok kecil adalah 6 orang peserta didik kelas X jenjang SMA. Hasil penelitian menunjukkan bahwa: 1) validitas LKPD berdasarkan uji pakar memiliki kategori valid dengan rata-rata keseluruhan 3,59; 2) kepraktisan isi LKPD memiliki kategori baik dengan rata-rata keseluruhan 3,70 dan kepraktisan harapan LKPD berdasarkan respon peserta didik memiliki kategori sangat baik dengan rata-rata keseluruhan 88,70%; dan 3) keefektifan LKPD berdasarkan penilaian keterampilan berpikir kritis peserta didik dalam mengerjakan LKPD memiliki kategori baik (meliputi interpretasi) dan kategori sangat baik (meliputi analisis, evaluasi, inferensi, eksplanasi dan pengaturan diri). Keterampilan interpersonal (bekerjasama) peserta didik memiliki kategori sangat baik dengan skor 86,33% dan keterampilan intrapersonal (teliti) peserta didik memiliki kategori sangat baik dengan skor 88,33%.